2020
DOI: 10.7717/peerj.9377
|View full text |Cite
|
Sign up to set email alerts
|

Temperature alters the shape of predator–prey cycles through effects on underlying mechanisms

Abstract: Background Predicting the effects of climate warming on the dynamics of ecological systems requires understanding how temperature influences birth rates, death rates and the strength of species interactions. The temperature dependance of these processes—which are the underlying mechanisms of ecological dynamics—is often thought to be exponential or unimodal, generally supported by short-term experiments. However, ecological dynamics unfold over many generations. Our goal was to empirically document shifts in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 65 publications
4
34
0
Order By: Relevance
“…coevolved predator-prey and host-natural enemy association under high temperature stress [ 34 , 35 ]. It is nevertheless critical to directly investigate and establish predator-prey interaction dynamics under varied temperatures [ 90 , 91 ] and how optimal performance may relate to CTLs. This will allow for a more effective assessment of constraints of biological control associated with thermal stress prior to organismal loss of physiological function, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…coevolved predator-prey and host-natural enemy association under high temperature stress [ 34 , 35 ]. It is nevertheless critical to directly investigate and establish predator-prey interaction dynamics under varied temperatures [ 90 , 91 ] and how optimal performance may relate to CTLs. This will allow for a more effective assessment of constraints of biological control associated with thermal stress prior to organismal loss of physiological function, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The strength of feeding interactions, in particular, increases with temperature, as feeding rates increase among consumers to compensate for increasing metabolic demands (Dell et al, 2011;Gillooly et al, 2001). Stronger predation in turn leads to declines in prey abundance and total biomass (Barneche et al, 2021;DeLong & Lyon, 2020;Garzke et al, 2019;Gilbert et al, 2014). Because gross respiration rates are determined by standing biomass, temperature effects on predation may ultimately influence ecosystem-level processes such as community respiration rates (O'Connor et al, 2009), and thus mediate the temperature response of microbial respiration rates worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…However, with a global biomass 200 times larger than that of nematodes (Bar-On et al, 2018), unicellular eukaryotes -collectively known as 'protists' -likely play a major role in regulating microbial communities at global scales (Oliverio et al, 2020) through bacterivory (Erktan et al, 2020;Gao et al, 2019). Ciliate protists, in particular, are wellknown bacterivores (Foissner & Berger, 1996), their population dynamics and feeding interactions are strongly temperature-dependent (DeLong & Lyon, 2020), and they are present in all major ecosystems (Foissner & Berger, 1996;Oliverio et al, 2020). As such, predation of microorganisms by protists can mediate the temperature response of microbial communities (Gao et al, 2019;Geisen et al, 2021), although this phenomenon has only been shown for one species of protist in soils (Geisen et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Kalinkat et al (2013) examined the effects of predator and prey body sizes on the functional response across 25 different predator species feeding on eight differently sized prey species requiring 2,564 experimental units. Finally, foraging rates depend on both abiotic and biotic conditions (Abrams & Ginzburg, 2000;Gilbert et al, 2014;Preston et al, 2018;DeLong & Lyon, 2020), so identifying the way in which temperature, predator density, or habitat complexity, for example, influence the functional response generates the same level of replication challenge.…”
Section: Introductionmentioning
confidence: 99%